What Does the Future Hold for the Treatment of FLT3-Mutated AML? News and Insights from ASH 2024 - Marcus M. Schittenhelm (healthbook TIMES. Oncology Hematology)
This mini review explores the evolution of FMS-like tyrosine kinase 3 (FLT3) inhibitor therapy and the current treatment landscape for *FLT3*-mutated acute myeloid leukemia (AML), summarizing insights from the 66th Annual ASH Meeting and Exposition 2024. It highlights the transition from first-generation therapies such as midostaurin to second-generation agents such as gilteritinib, crenolanib and quizartinib. Midostaurin, the first FLT3-targeting therapy approved for newly diagnosed *FLT3*-mutated AML, laid the foundation for FLT3 inhibition by demonstrating survival benefits when combined with chemotherapy. Gilteritinib has emerged as a standard for relapsed/refractory (R/R) AML, crenolanib shows efficacy in post-transplant maintenance and quizartinib demonstrates promise in reducing frontline relapse risk. These advancements have improved outcome of *FLT3*-mutated AML in recent years while emphasizing the need for ongoing innovation to tackle relapse and resistance.